Pushing the Electrochemical Performance Limits of Polypyrrole Toward Stable Microelectronic Devices - Tahir, Muhammad; He, Liang; Li, Lihong; Cao, Yawei; Yu, Xiaoxia; Lu, Zehua; Liao, Xiaoqiao; Ma, Zeyu; Song, Yanlin (Nano-Micro Letters, 2023)
Conducting polymers have achieved remarkable attentions owing to their exclusive characteristics, for instance, electrical conductivity, high ionic conductivity, visual transparency, and mechanical tractability. Surface and nanostructure engineering of conjugated conducting polymers offers an exceptional pathway to facilitate their implementation in a variety of scientific claims, comprising energy storage and production devices, flexible and wearable optoelectronic devices. A two-step tactic to assemble high-performance polypyrrole (PPy)-based microsupercapacitor (MSC) is utilized by transforming the current collectors to suppress structural pulverization and increase the adhesion of PPy, and then electrochemical co-deposition of PPy-CNT nanostructures on rGO@Au current collectors is performed. The resulting fine patterned MSC conveyed a high areal capacitance of 65.9 mF cm−2 (at a current density of 0.1 mA cm−2), an exceptional cycling performance of retaining 79% capacitance after 10,000 charge/discharge cycles at 5 mA cm−2. Benefiting from the intermediate graphene, current collector free PPy-CNT@rGO flexible MSC is produced by a facile transfer method on a flexible substrate, which delivered an areal capacitance of 70.25 mF cm−2 at 0.1 mA cm−2 and retained 46% of the initial capacitance at a current density of 1.0 mA cm−2. The flexible MSC is utilized as a skin compatible capacitive micro-strain sensor with excellent electromechanochemical characteristics. Highlights: 1 Optimizing the current collectors with rGO and the addition of CNT in PPy, and the structural pulverization is prevented significantly. 2 Areal capacitances of 65.9 to 70 mF cm−2 are achieved for PPy-CNT@rGO microsupercapacitors (MSCs) with 79% capacitance retention after 10,000 cycles. 3 The MSC-derived capacitive micro-strain sensor is capable of biosignals detection. 4 The micro strain sensor is capable of detecting wide levels of applied strain with short response/recovery time and excellent reliability.